The design of an intervention programme to address the prevalence of obesity and physical fitness of adolescents attending high school - Naidoo, Shane (Division of Physiotherapy, 2022)
Background: South Africa has the highest prevalence rate (8.3%) of childhood obesity in sub-Saharan Africa. Obesity is a complex condition to control as it has environmental, as well as genetic factors that influence its prevalence. Childhood obesity, a rising problem worldwide and within South Africa, has been negatively linked with both physical fitness and physical activity. PA and school-based nutrition intervention programmes have been shown to have positive effects on diet and PA behaviours in children. However, there is minimal literature reporting on the effectiveness of school-based interventions in a South African setting. The aim of this study was to determine the prevalence of obesity, levels of physical fitness and physical activity in adolescents attending school in an urban setting. Together with the literature, an intervention programme was designed addressing key outcome measures identified from the sample. Methodology: The study was conducted in two phases. Ten schools were randomly selected from the school education district in KwaZulu-Natal Department of Education (KZNDoE) for phase one. A total of 400 eligible students were identified by the respective school teachers and parental consent was obtained, with assent obtained from the participants. A sample of 278 (girls n = 150, boys n = 128) participants with a mean age of 15yrs 1 month (CI 95% 12,1 – 17.1 and SD 1.14), was measured for height, weight, hip circumference, waist circumference and physical fitness (standing broad jump, sit-ups in 30s, hand grip strength, sit-and-reach and 20m shuttle run). BMI and WHR were calculated using anthropometric measurements. Physical activity (PA) was self-reported using the Physical Activity Questionnaire for Adolescents (PAQ-A) and the International Study of Childhood Obesity, Lifestyle and the Environment (ISCOLE) demographic form were completed by the participants' guardians/parents. Phase two involved the design of a PA intervention programme using evidence-based outcome measures from previous studies and problem areas identified in this study. Results: The mean BMI z-score was 0.30 (CI 95% 0.12 to 0.49) with boys displaying a mean of 0.19 (CI 95% -0.89 to 0.46) and girls 0.39 (CI 95% 0.15 to 0.65). There was a 16.2% prevalence of overweight (1 < BMI-z score ≤ 2), 13.3% prevalence of obesity (2 < BMI-z score ≤ 3) and 2.9% prevalence of morbid obesity (3 < BMI-z score ≤ 4). Mean WHR for the sample was 0.82 (CI 95% 0.81 – 0.83). Low levels of PA were reported by 45% (girls n = 83, boys n = 42) of the sample and 53.6% (girls n = 66, boys n = 83) reported moderate levels of PA. Girls in the sample had a higher mean sit-and-reach (t = 4.68, p < 0.05) and hand grip strength (t = 5.49, p < 0.05) than the normative values. Boys in the sample had higher mean (t = 13.2, p < 0.05) sit-and-reach than normative values. Multiple regression models were applied and BMI was found to be an inverse predictor for sit-ups ß = -0.07 (p < 0.05, CI 95% -1.0 to -0.03) and broad jump ß = -0.01 (p < 0.05, CI 95% -0.01 to -0.005). BMI was also a direct predictor for hand grip strength ß = -0.07 (p < 0.05, CI 95% 0.05 to 0.09). Discussion: The 16.2% prevalence of obesity was higher than the reported 8.5% in another South African study on adolescent scholars and the national reported level of 5.5%. The waist-hip ratio (WHR) was lower than the national reference level of 0.84 and higher compared to values obtained from adolescents in Europe (comparisons were made to age and gender specific normative values obtained in Europe, as there are no national reference physical fitness values for adolescents). Girls displayed lower values in three of the five physical tests (standing broad jump, sit-ups and 20m shuttle run), while boys displayed lower values for four (standing broad jump, hand grip strength, sit-ups and 20m shuttle run) of the five physical fitness tests. PA is indirectly correlated with BMI, and with BMI being a predictor for physical fitness, the promotion of PA amongst adolescents is imperative and urgent to curb the growing prevalence of obesity. Using evidence from previous research an intervention programme was designed to address the problems areas identified. These were high prevalence of obesity and overweight, low PA levels, poor cardiovascular function , low muscular power and poor muscular endurance across the sample. Boys also exhibited low levels of muscular strength than the normal population mean. PA programmes must be 60 minutes of duration implemented at least three times per week over 12 weeks minimum in order to have a reduction in BMI. Programmes should incorporate aerobic and anaerobic training as concurrent training has shown best results for decreasing BMI. The aerobic component of the programme must include a high intensity interval training (HIIT) as this has positive benefits on cardiovascular markers. The anaerobic component must include free weights as this showed better improvements than using resisted exercise devices in body composition, increases in upper and lower limb muscle strength in boys and improved lower limb muscle power especially in girls. Programmes should be implemented in schools with trained instructors and incorporate the family as a combination of these showed favourable compliance and overall better outcome measures. PA programmes that have a circuit formation and that incorporate a fun element has also shown to have better outcome measures and compliance. Conclusion: Physical activity levels are on the decline and obesity prevalence is on a rapid upward trajectory amongst South African adolescents. These trends could be ominous for the next workforce generation as these have been linked to numerous non-communicable diseases where the already constrained health system is placed under added pressure. PA programmes should be incorporated into schools' curricula as this may be a viable way to implement successful interventions to address obesity, physical fitness and physical activity.